Keragaan Usaha Badan Kredit Kecamatan (Studi di Kalimantan Selatan) - Dolok Saribu (AGRIDES: Jurnal Agribisnis Perdesaan, 2012)
The study aims are: (1) knowing the efficiency of business of Badan Kredit Kecamatan (BKK), as well as the factors influence it; (2) to obtain the optimal picture of the income scale in each Badan Kredit Kecamatan; and (3) knowing the condition of Badan Kredit Kecamatan that measured by the liquidity ratio, solvency, and rentability, in the business district and the impact of the credit agencies on the technical efficiency. The primary data were collected from all (30) credit agencies in the 5 counties and secondary data collected from Bank Pendapatan Daerah. The technical efficiency was determained by the approach of deterministic production function frontier with the function of rayhomothetic whereas the financial analysis performed by the ratios. The results showed that all free variables were directly proportional and have real effect on the gross revenue of Badan Kredit Kecamatan. From the efficiency measuring, it was known that 93.33% of BKK have smaller efficiency index rather than the mean index of efficiency. About 76.67% of BKK were in a state of decreasing return to scale, which means that Badan Kredit Kecamatan in South of Kalimantan was not been efficient yet. That meant that the integration between input factor and technology used has not been reached the optimum, yet. The efficiency of Badan Kredit Kecamatan, significantly and positively, influenced by the state of liquidity and the number of business customer units that trained by the Badan Kredit Kecamatan, while solvability factors showed negative effect on the efficiency. With the condition of the BKK, it can be concluded that the BKK in South of Kalimantan is should to be increased.